333. THE EGIDIUS PROJECT: A NETWORK APPROACH TOWARDS EXCELLENT MULTIDISCIPLINARY QUALITY OF CARE FOR PATIENTS WITH ESOPHAGEAL AND GASTRIC CANCER. (24th September 2022) - Geerts, Julie; Wijnhoven, Bas; Rosman, Camiel; Verhoeven, Rob; Nieuwenhuijzen, Grard; ,
Abstract: Diagnosis and treatment of esophageal and gastric cancer is complex and requires a multidisciplinary network approach involving multiple hospitals in the Netherlands. Recent studies have shown that there is still substantial practice variation and variation in outcomes. The aim of this project is to improve quality of care in oncological networks for patients with esophageal or gastric cancer for every disease stage and to minimize undesirable practice variation and improve outcomes. To achieve excellent quality of care of all participants in an oncological network, a multidisciplinary improvement process has been initiated involving all participating hospitals. The pilot project has started in three networks comprising 20 hospitals. First, physicians from different specialties (surgery, oncology, radiotherapy and gastro-enterology), patient advocates and health insurance representatives determined the most important quality-of-care indicators to be measured prospectively. Second, Plan-Do-Check-ACT (PDCA) cycles will be established to evaluate process and outcome indicators with both professionals and patients, leading to improvement processes to be initiated. These will be evaluated quarterly. Specialists and patient representatives have defined a list of quality-of-care indicators for all hospitals within this project: four indicators on gastroenterology, three for radiotherapy, four surgical indicators, six on medical oncology and six on the overarching care pathway. See table 1 for the full list of indicators. The prospective measurements will start May 2022. The first results and PDCA-cycles are expected to take place in June 2022. It is expected to lead to new insights in hospital variation in the Netherlands and to start an improvement process which will be agreed upon in the upcoming discussions. A unique network multidisciplinary project involving physicians as well as patient and health insurance representatives has been initiated. Novel and existing specialty-specific and general quality-of-care indicators haven been defined. The quarterly evaluations of this specific set of indicators to assess practice performance and variation is expected to lead to new insights, improve outcomes and reduce undesirable practice variation within the Netherlands.